Who benefits from the minimum wage–natives or migrants? - Madeline Zavodny (IZA World of Labor, 2014)
According to economic theory, a minimum wage reduces the number of low-wage jobs and increases the number of available workers, allowing greater hiring selectivity. More competition for a smaller number of low-wage jobs will disadvantage immigrants if employers perceive them as less skilled than native-born workers–and vice versa. Studies indicate that a higher minimum wage does not hurt immigrants, but there is no consensus on whether immigrants benefit at the expense of natives. Studies also reach disparate conclusions on whether higher minimum wages attract or repel immigrants.
Keywords: J61; J38; J15; 330; minimum wage; immigrants; low-skilled workers